Hubungan Perhatian Orang Tua Dengan Kepercayaan Diri Anak Kelompok B Di Paud Se-Gugus Kembang Sepatu Kecamatan Muara Bangkahulu Kota Bengkulu - zuliyani, mawar; nasirun, nasirun; wembrayarli, wembrayarli (UNIB Press, 2022)
The purpose of this study was to determine the correlation between parental attention and the self-confidence of group B children in early childhood education Segugus Kembang Sepatu Kecamatan Muara Bangkahulu Bengkulu City. Muse a correlational quantitative approach. The population was 148 and the sample was 44 parents with a sampling technique using proportional random sampling. Data collection techniques use questionnaires. Analysis of research data is a correlation of product moments. The results showed parental attention from 5 sub-indicators (guidance and advice, supervision, giving rewards and punishments, accompanying children to learn, and creating a conducive home) with an average score of 3,011 in the low category and the self-confidence of children from 4 subs (optimistic, responsible, independent and reacting positively in facing various problems) with an average score of 2,861 in the low category. There is a significant relationship between parental attention and children's self-confidence. It is recommended that subsequent researchers look for children's self-confidence factors with other factors.